The 10-Year Prognosis and Prevalence of Brugada-Type Electrocardiograms in Elderly Women: A Longitudinal Nationwide Community-Based Prospective Study. Issue 6 (November 2020) - Yeh, Sherri Shih-Fan; Chen, Ching-Yu Julius; Wu, I-Chien; Hsu, Chih-Cheng; Chen, Tzu-Yu; Tseng, Wei-Ting; Tang, Feng-Cheng; Wang, Chi-Chung; Juan, Chung-Chou; Chiu, Hou-Chang; Lo, Huey-Ming; Yang, Dun-Hui; et al.
Abstract : Background: Brugada syndrome is a disorder associated with sudden cardiac death and characterized by an abnormal electrocardiogram (ECG). Previous studies were predominantly conducted in men, and the data on long-term prognosis are limited. Information about women, especially elderly women, is lacking. Objective: The aim of this study was to investigate the long-term prognosis of the Brugada ECG pattern in elderly women. Method: We investigated the 10-year prognosis of the Brugada ECG pattern in elderly women in a nationwide community-based population in Taiwan. Community-dwelling women older than 55 years were prospectively recruited from December 2008 to March 2013 by a stratified random sampling method. All enrolled individuals were followed up annually until April 2019, and the cause of death was documented by citizen death records. Results: Among 2597 women, 60 (2.31%) had a Brugada-type ECG, and this prevalence was higher than the mean global prevalence of 0.23%. One woman had a type 1 ECG (0.04%), whereas 15 (0.58%) and 44 (1.70%) women had type 2 and type 3 ECG patterns, respectively. Cox survival analysis revealed that all-cause mortality and cardiac mortality were similar in the individuals with and without a Brugada-type ECG during a mean follow-up of 96.1 ± 20.5 months. Conclusions: Our findings suggest that Brugada ECG patterns are not infrequent in elderly women but are not associated with increased risk of mortality in long-term follow-up; these findings may help reduce unnecessary anxiety for physicians, nurses, allied health caregivers, and patients. Abstract : Supplemental digital content is available in the text.